Validitas LKPD Berdiferensiasi Materi SPLDV Untuk Mendukung Kemampuan Computational Thinking Dengan Konteks Lokal Musi Banyuasin - Dayanti, Windy Rama; Mulyono, Budi; Hapizah, Hapizah (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop Student Worksheets (LKPD) through differentiation learning to support students' computational thinking skills in studying and understanding the material of two-variable linear equation systems. Computational Thinking skills include several important elements such as decomposition, pattern recognition, abstraction, and algorithmic thinking. Differentiation learning is designed to accommodate the diversity of interests, learning styles and abilities of each student. This study uses the Research and Development (R&D) method with the ADDIE model consisting of five stages, namely: analysis, design, development, implementation, and evaluation. There is a validation process included in the development stage, the validation process is carried out by researchers together with an expert review (validator) consisting of 2 lecturers from the mathematics education study program at Raden Fatah State Islamic University, Palembang and 1 mathematics teacher. The validation results show that the score obtained in the content aspect is 3.90 with valid criteria results. in the construct aspect, they got a score of 4.10 with valid criteria results, and they got a score of 4.21 in the language aspect with very valid criteria results. Based on these findings, the differentiation-based LKPD developed in the context of Musi Banyuasin local wisdom was declared valid and suitable for use to support increasing students' computational thinking abilities